Enhancement of Hip Joint Flexibility using Flexor and Unilateral Exercises (British Journal of Multidisciplinary and Advanced Studies, 2024)
Improved hip flexibility is essential for enhanced overall fitness, ensuring balance and a broader range of motion. Therefore, the understanding of how limited hip movement and physical activity can affect performance and increase injury risk due to a lack of flexibility. Thus, this investigation determined the effectiveness of interventions, namely Flexor and Unilateral Exercises, in enhancing the hip-joint flexibility of the participants. The study involved 86 males and 80 females aged 15 to 18, utilizing a two-factor pretest-posttest quasi-experimental research design. Results indicated a significant difference in the pretest and posttest hip joint flexibility of the two groups, Flexor and Unilateral. Post-interventions, significant improvements in hip joint flexibility were evident in both groups. Additionally, the result revealed a noteworthy difference with a significant effect size between pretest and posttest flexibility measures for both the Flexor and Unilateral groups, emphasizing the effectiveness of each intervention. Notably, hip Flexor exercises yielded a considerably higher increment in hip range of motion compared to Unilateral exercises, indicating their superior impact. The two interventions distinctively and significantly enhanced hip joint flexibility, warranting further investigation into the nuances of hip joint range of motion and overall flexibility across genders. This exploration should include a thorough assessment of the intervention's efficacy for both men and women.